2018
DOI: 10.1002/adma.201800957
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Exchange Processes between Oxide Memristive Devices and Water Molecules

Abstract: Resistive switching based on transition metal oxide memristive devices is suspected to be caused by the electric-field-driven motion and internal redistribution of oxygen vacancies. Deriving the detailed mechanistic picture of the switching process is complicated, however, by the frequently observed influence of the surrounding atmosphere. Specifically, the presence or absence of water vapor in the atmosphere has a strong impact on the switching properties, but the redox reactions between water and the active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 44 publications
1
49
0
Order By: Relevance
“…For example, electrical measurements in different atmospheres allowed to unveil the n-type conductive path responsible resistive switching in MgO core-TiO 2 shell nanowires. [200][201][202][203] Using a completely different approach, resistive switching was observed also considering conductive nanowires covered by an oxidized shell layer, in which the switching occurs along the radial direction of the NW. It is important to remark that this strategy can be adopted only in planar devices and not in widely studied capacitor-like devices where the switching mechanism is hidden in stacked sandwich structures: for these reasons, nanowires can be considered a good platform to investigate the resistive switching mechanism in a wide range of materials.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…For example, electrical measurements in different atmospheres allowed to unveil the n-type conductive path responsible resistive switching in MgO core-TiO 2 shell nanowires. [200][201][202][203] Using a completely different approach, resistive switching was observed also considering conductive nanowires covered by an oxidized shell layer, in which the switching occurs along the radial direction of the NW. It is important to remark that this strategy can be adopted only in planar devices and not in widely studied capacitor-like devices where the switching mechanism is hidden in stacked sandwich structures: for these reasons, nanowires can be considered a good platform to investigate the resistive switching mechanism in a wide range of materials.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%
“…Rectification is characteristic of a Schottky diode, which is governed by the metal contact with the higher work function being in our case Pt. [16,18] Also initial studies by Messerschmitt et al show that the maximum current during the set process drops with humidity. This direction emerges only after lowering the humidity level to 5% RH where a current decrease at positive applied bias of about five orders of magnitude is observed.…”
Section: Humidity Influence On Device's I-v Characteristicsmentioning
confidence: 99%
“…[10] Changes of resistance states in the oxides are facilitated by ion transport under high local electrical fields. [1] Recently however, it has been shown that also the change in the relative humidity in the surrounding atmosphere will change the resistive switching behavior of TaO x , [13,14] HfO x , [13] SrTiO 3 , [15,16] and TiO 2 . [11] In general oxidebased memristive devices work on the principle of nonvolatile resistance change upon the application of an electrical potential.…”
Section: Investigation Of the Eightwise Switching Mechanism And Its Smentioning
confidence: 99%
See 1 more Smart Citation
“…The ions participating in the RS are anions, typically oxygen ions (or oxygen vacancies). Other than ECM cells, where the sources of cations are primarily the active electrode or nanoparticles in the switching layer matrix, oxygen ions in VCM cells are mainly from the external atmosphere, such as oxygen and water molecules, and the switching layer matrix. Without the oxygen‐containing atmosphere, for example, in pure N 2 , stable RS can hardly occur .…”
Section: High‐speed and Scalable Rram Cells And Systemsmentioning
confidence: 99%